Assesment of Boron Neutron Capture Therapy (BNCT): Compact Neutron Generators - Nur Setyo Wahyuni; Yohannes Sardjono (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2018)
Boron Neutron Capture Therapy (BNCT) is an effective and promising treatment of tumour types which are resistant to conventional therapies. The characteristics of boron neutron capture therapy (BNCT) for cancer treatment demand, in addition to sufficient fluxes of epithermal neutrons, proper conditions of the neutron sources—compact layout, flexible operation, compatibility with hospital setting, etc. The lack of proper neutron sources that can be integrable to the infrastructure of hospital or clinical facilities is a major problem. Compact neutron generators (CNGs), which are the most compact and least expensive, were a potential, alternative, solution to existing BNCT treatment facilities based on nuclear reactors. This paper will provide information about the latest CNGs technology development that has contributed to the Boron Neutron Capture Therapy (BNCT) technology improvement.